Nationality as a risk factor of tuberculosis resistance in two co-related countries (Bangladesh Journal of Medical Science, 2018)
Background: Republic of Azerbaijan and Iran are two neighboring countries with high amount of travelling between them, different rates of TB and its resistance. These relationships could complicate the controlling of tuberculosis programs.Objective: The study was conducted to determine the prevalence of tuberculosis (TB) resistance and its risk factors in the two geographically co-related regions.Method: A total of 119Mycobacterium tuberculosis isolates from the patients of the target regions (Azerbaijan Rep. and Tabriz, Iran) were examined at the Central Tuberculosis Laboratory in Tabriz, Iran. The cultures and drug susceptibility tests was performed on Lowenstein-Jensen. All the isolates were categorized by MIRU-VNTR molecular method into clustered and un-clustered groups. The clustering as well as demographic data were analyzed to determine the risk factors contributing to TB resistance. The categorical data about the TB resistance were compared using a chi square test.Results: 27.8 percent of isolates were resistant at least to one of the 1st line of anti-tuberculosis drugs. The prevalence of any drug resistance and MDR were 64.6 and 17.9 percent respectively for Azari isolates, where the rate of resistance to rifampin and isoniazid was higher than streptomycin and ethambutol. The corresponding figures for the isolates from Tabriz were 16.9 and 3.3 percent respectively.Conclusions: The results of this comparative and cross-sectional study showed statistically significant differences in TB resistance between the isolates from the patients of Azerbaijan Rep. and Iran. According to the results, the rate of resistance to RMP, INH, and MDR was higher in Azerbaijan; consequently, nationality could be regarded as a risk factor of MDR, resistance to RMP and INH but not to SM and ETB. Other studied parameters did not contribute to TB resistance.Bangladesh Journal of Medical Science Vol.18(1) 2019 p.36-41